Struktur Dan Fungsi Ungkapan Kepercayaan Masyarakat Nagari Koto Kaciak Kecamatan Bonjol Kabupaten Pasaman - Yulia Novita; Gemarni Tatalia, Ricci; Samsiarni (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
The purpose of this study is to describe the structure and function of expressions of community trust in Nagari Koto Kaciak, Bonjol District, Pasaman Regency. This study describes the structure and function that exist in expressions of trust, where the category is focused on the structure of expressions of community trust. This research design is qualitative research using descriptive analysis methods. Data was collected through interview and recording techniques. Based on the research that has been conducted, twenty-four expressions of trust were found in the people of Nagari Koto Kaciak, Bonjol District, Pasaman Regency. The found confidence expression function consists of: 1) the function of thickening religious emotions as much as 3 data, 2) the function of educational tools for children or adolescents as many as 19 data, 3) the function as an acceptable explanation of a folk's sense to natural symptoms as much as 4 data, and 4) the function as comforting people who are experiencing disaster as much as 1 data.